Analisa Perilaku Pasar Terhadap Purchase Intention Of Premium Sportswear ( Footwear & Apparel ) Brand â€œ Xâ€ Melalui Online Shopping Di Pulau Jawa, Indonesia - Kurniawan, Ellihu Yona; Bayu Dirgantara, I Made (ITB AAS Indonesia Surakarta, 2023)
This research aims to analyze market behavior regarding purchase intention of premium Sportswear (Footwear & Apparel) brand